2015
DOI: 10.1016/j.dib.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Data for comparative proteomics analysis of the antitumor effect of CIGB-552 peptide in HT-29 colon adenocarcinoma cells

Abstract: CIGB-552 is a second generation antitumor peptide that displays potent cytotoxicity in lung and colon cancer cells. The nuclear subproteome of HT-29 colon adenocarcinoma cells treated with CIGB-552 peptide was identified and analyzed [1]. This data article provides supporting evidence for the above analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Similar patterns of protein bands were obtained after the SDS-PAGE analysis of nuclear fractions of both, control and CIGB-552 treated cells (See Figure 3 in [13]). The study was performed using the DF-PAGE method [10,11,15] (See Figure 2 in [13]). DF-PAGE combines protein fractionation by SDS-PAGE, ingel protein digestion and peptide fractionation by SDS-free PAGE.…”
Section: Df-pagementioning
confidence: 86%
See 4 more Smart Citations
“…Similar patterns of protein bands were obtained after the SDS-PAGE analysis of nuclear fractions of both, control and CIGB-552 treated cells (See Figure 3 in [13]). The study was performed using the DF-PAGE method [10,11,15] (See Figure 2 in [13]). DF-PAGE combines protein fractionation by SDS-PAGE, ingel protein digestion and peptide fractionation by SDS-free PAGE.…”
Section: Df-pagementioning
confidence: 86%
“…This showed that 466 of the identified proteins, including 49 differentially modulated, can localize to nucleus (See Table 2 in [13]). The detection of not nuclear localized proteins suggests that contamination occurred during fraction enrichment.…”
Section: Subcellular Location Of Identified Proteinsmentioning
confidence: 94%
See 3 more Smart Citations